Pengaplikasian Sistem Website Absensi Magang Pada Kantor Dinas Pemuda Dan Olahraga (Dispora) Palembang Sumatera Selatan - Muhamad Dyo Arganata; Irman Effendy; Ahmad Mutatkin Bakti; Ahmad Syazili (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The internship participant attendance process at the Palembang, South Sumatra Youth and Sports Agency (DISPORA) Office was previously conducted manually, potentially leading to problems such as delays in recording, data errors, and difficulties in generating attendance reports. This study aims to implement a website-based internship attendance system that can improve the effectiveness, efficiency, and accuracy of managing internship participant attendance data. The system development method used is the Waterfall method, which includes needs analysis, system design, implementation, testing, and maintenance. The system was built using the PHP programming language and a MySQL database and is accessible via the internet. The results of this study indicate that the website-based internship attendance system simplifies the attendance recording process, minimizes data errors, and accelerates the attendance report generation process. With the implementation of this system, it is hoped that the management of internship participant attendance at DISPORA Palembang, South Sumatra will be more structured, transparent, and accurate.